2020
DOI: 10.1038/s41598-020-76462-y
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the differences in oxidation of high-performance α- and β- diisobutylene biofuels via Synchrotron photoionization mass spectrometry

Abstract: Biofuels are a promising ecologically viable and renewable alternative to petroleum fuels, with the potential to reduce net greenhouse gas emissions. However, biomass sourced fuels are often produced as blends of hydrocarbons and their oxygenates. Such blending complicates the implementation of these fuels in combustion applications. Variations in a biofuel’s composition will dictate combustion properties such as auto ignition temperature, reaction delay time, and reaction pathways. A handful of novel drop-in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
1
1
0
Order By: Relevance
“…Therefore, the added steric contribution for the radical intermediate results in a higher BDE value for the central carbon vs. the primary carbon. The BDE trends presented here agree with the computed BDE trends by Terracciano et al [10] . The next Sections 3.2 to 3.4 de- scribe how the rate constants for the high-temperature reactions classes were obtained for the chemical kinetic model.…”
Section: Computational Detailssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the added steric contribution for the radical intermediate results in a higher BDE value for the central carbon vs. the primary carbon. The BDE trends presented here agree with the computed BDE trends by Terracciano et al [10] . The next Sections 3.2 to 3.4 de- scribe how the rate constants for the high-temperature reactions classes were obtained for the chemical kinetic model.…”
Section: Computational Detailssupporting
confidence: 91%
“…Recent work by Terracciano et al [10] examined both DIB-1 and DIB-2 at stoichiometric conditions and at atmospheric pressure in a jet-stirred reactor and identified intermediates using tuneable vacuum ultraviolet (VUV) and time-of-flight mass spectrometry. They found that the ignition characteristics were greatly dependent on C 4 and C 7 fragment production and decomposition for both isomers and that the tert-butyl radical was a dominant intermediate species.…”
Section: Introductionmentioning
confidence: 99%